Pathogenic Mechanisms of Fusobacterium nucleatum on Oral Epithelial Cells - Groeger, Sabine; Zhou, Yuxi; Ruf, Sabine; Meyle, Joerg (Frontiers in Oral Health, 2022)
Periodontitis is an oral chronic inflammatory disease and may cause tooth loss in adults. Oral epithelial cells provide a barrier for bacteria and participate in the immune response. Fusobacterium nucleatum (F. nucleatum) is one of the common inhabitants of the oral cavity and has been identified as a potential etiologic bacterial agent of oral diseases, such as periodontitis and oral carcinomas. F. nucleatum has been shown to be of importance in the development of diverse human cancers. In the dental biofilm, it exhibits a structural role as a bridging organism, connecting primary colonizers to the largely anaerobic secondary colonizers. It expresses adhesins and is able to induce host cell responses, including the upregulation of defensins and the release of chemokines and interleukins. Like other microorganisms, its detection is achieved through germline-encoded pattern-recognition receptors (PRRs) and pathogen-associated molecular patterns (PAMPs). By identification of the pathogenic mechanisms of F. nucleatum it will be possible to develop effective methods for the diagnosis, prevention, and treatment of diseases in which a F. nucleatum infection is involved. This review summarizes the recent progress in research targeting F. nucleatum and its impact on oral epithelial cells.